Direct Visualization of Transient Thermal Response of a DNA Origami - Song, Jie; Arbona, Jean-Michel; Zhang, Zhao; Liu, Lei; Xie, Erqing; Elezgaray, Juan; Aime, Jean-Pierre; Gothelf, Kurt Vesterager; Besenbacher, Flemming; Dong, Mingdong (Journal of the American Chemical Society, 2012)
The DNA origami approach enables the construction of complex objects from DNA strands. A fundamental understanding of the kinetics and thermodynamics of DNA origami assembly is extremely important for building large DNA structures with multifunctionality. Here both experimental and theoretical studies of DNA origami melting were carried out in order to reveal the reversible association/disassociation process. Furthermore, by careful control of the temperature cycling via in situ thermally controlled atomic force microscopy, the self-assembly process of a rectangular DNA origami tile was directly visualized, unveiling key mechanisms underlying their structural and thermodynamic features.